Effects of Transfer of Right and Jurisdictional Boundary on Mining Reclamation Performance in East Kalimantan Forest Areas - Rina Kristanti; Hariadi Kartodihardjo; Bramasto Nugroho; Irdika Mansur (Institut Pertanian Bogor (IPB University), 2020)
Mining is still considered to be an essential sector to gain national income and to provide energy supply. Forest Leasehold License (FLL) is a mechanism to accommodate the non-forestry sector, including mining development in the forest area. This license is a form of transfer of right given from Minister of Environment and Forestry to a mining license holder. Transfer of right by FLL contractual shaped jurisdictional boundary that is one of the obligations that has to be complied by FLL holder is to conduct mining reclamation. This study aimed to analyze the effects of FLL and its jurisdictional boundary on mining reclamation performance in East Kalimantan forest areas. It is a descriptive qualitative study based implemented the agency theory with the institutional approach. The study found that mining permit and FLL is a temporary transfer of right. The emerging problem in the FLL and its jurisdictional boundary related to asymmetric information and transaction cost caused moral hazards such as adverse risk selection of FLL holders by the principal, reclamation ignorance by the agent, and opportunism both from principal and agent. These agency problems affect FLL reclamation performance that just reached 41.35% over disturbed areas. Institutional challenges are due to the regulation gap creating a conflict of interest, budget and human resource constrain, cost center activity, and lack of economic incentive as well as lack of coordination among the government institutions. The research findings suggested inputs for institutional arrangement in terms of transfer of the right, including FLL reclamation process business, to improve its performance in the East Kalimantan forest area.